THE IMPORTANCE OF OBESITY IN THE DEVELOPMENT OF CORONARY HEART DISEASE (World Bulletin of Public Health, 2025)
Obesity is one of the most common chronic diseases in the world, which leads to the development of cardiovascular diseases. Epidemiological studies have established that there is an association between the prevalence of obesity and the increase in other diseases. This article examines the development of coronary heart disease in overweight and obese adult patients by interpreting the results of electrocardiography and body weight by measuring weight (kg) and height (cm2 ).